Concurso Rainha da soja: atos e gestos da beleza feminina em Ponta Grossa, Paraná (década de 1970) (Revista de História Regional, 2008)
This article aims to present the acts and the gestures that instituted the Soybean Queen Contest in Ponta Grossa, Paraná, between 1971 and 1980. These considerations result from the first approaches to the theme accomplished and try to reconstruct the event in its form, inserted in the socio-economic context of that time, at the local level as well as at the level of the military discourses regarding the production of soybean. The starting point was the principle that the contest was a space of symbols creation and reproduction, which instituted feminine behaviors. Complementary, from another view, it is possible to assume that the multinational company which sponsored and organized the contest looked at it as a space to obtain symbolic recognition and to share the art of living with the local community. With such thoughts underlying the analysis, this article was structured in three moments: the first focuses on the contextual specificities of Ponta Grossa; the second deals with the form taken by the contest; and finally, the third is an attempt to comprehend its content by rereading its meanings.